Density Based Traffic Light Controlling System using IOT - Bhagavan, K; Yaswitha Reddy, B; Krishna Sujay, T; Sravan Kumar, T (International Journal of Engineering and Technology, 2018)
The present existing frameworks do dominant the traffic becomes major issue owe to fast increase in vehicles and conjointly owing to giant time lag between the traffic lights. So, so as to improve the Â Â Â Â Â Â Â Â Â Â Â Â Â downside, I am going to opt for the effective traffic lights system using Density technique. This paper illustrate you how to manage traffic density. During this scheme, the sensing are adopted to live traffic substantially. we rearrange one LDR sensing element for each one road; these Light Dependent resistors sensors forever the traffic thereon specific roadway. of these LDR sensors are interfaced with micro controller. Supported controller & Sensors recognize traffic after that traffic system has been controlled.Â Â